THE MEANING AND IMPORTANCE OF FAIRY TALES - Ergasheva Durdona Safarali qizi (American Journals, 2023)
Fairy tale is an imaginative story or piece of literature told in a variety of media. Stories, which are based on magic and fantastical settings, plots, characters, and happy endings. A quality fairy tale tells a compelling story with a timeless theme. It can further be characterized by looking at the story elements (characters, plot, setting, theme, style, tone, and point of view) with quality characteristics and how they are combined to tell a story.
Keywords: phrase, teach lessons, great importance, local views, pedagogical idea.